2018
DOI: 10.1016/j.soilbio.2018.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Plant litter quality affects the accumulation rate, composition, and stability of mineral-associated soil organic matter

Abstract: Mineral-associated organic matter (MAOM) is a relatively large and stable fraction of soil organic matter (SOM). Plant litters with high rates of mineralization (high quality litters) are hypothesized to promote the accumulation of MAOM with greater efficiency than plant litters with low rates of mineralization (low-quality litters) because litters with high rates of mineralization maximize the synthesis of microbial products and most MAOM is microbial-derived. However, the effect of litter quality on MAOM is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
79
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(86 citation statements)
references
References 68 publications
(94 reference statements)
7
79
0
Order By: Relevance
“…The carbon to nitrogen (C:N) ratio of roots, which is critical to predict soil organic matter (SOM) dynamics, also varies across environments and growth stages. Root C:N ratio is the primary indicator of crop residue quality, which influences nutrient availability and SOM stabilization (Gentile et al, 2011b;Córdova et al, 2018) in the shortand long-term (Gentile et al, 2011a;Cotrufo et al, 2013;Sprunger et al, 2019). Although low C:N ratios are often assumed to promote nutrient release and SOM stabilization, results are inconsistent (Castellano et al, 2015) and a previous study indicated that the formation and stabilization of SOC is more affected by the quantity of residue inputs and their interaction with soil matrix than the quality of residue inputs (Gentile et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…The carbon to nitrogen (C:N) ratio of roots, which is critical to predict soil organic matter (SOM) dynamics, also varies across environments and growth stages. Root C:N ratio is the primary indicator of crop residue quality, which influences nutrient availability and SOM stabilization (Gentile et al, 2011b;Córdova et al, 2018) in the shortand long-term (Gentile et al, 2011a;Cotrufo et al, 2013;Sprunger et al, 2019). Although low C:N ratios are often assumed to promote nutrient release and SOM stabilization, results are inconsistent (Castellano et al, 2015) and a previous study indicated that the formation and stabilization of SOC is more affected by the quantity of residue inputs and their interaction with soil matrix than the quality of residue inputs (Gentile et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…First, plant tissue chemistry determines the availability of plant derived C that could be stabilized by physicochemical interactions in mineral soils . Plant tissue chemistry regulates decomposition rates of plant litter, substrate use efficiency by soil microbes, and the inherent “recalcitrance” and reactivity of plant biomolecules (e.g., Castellano, Mueller, Olk, Sawyer, & Six, ; Córdova et al, ; Mueller, Polissar, Oleksyn, & Freeman, ; Mueller et al, ). Thus, the stability of total SOM in mineral soils beneath different tree species could be positively correlated with indices of those species’ litter quality (e.g., low lignin to nitrogen ratios), because correspondingly high rates of litter decomposition and high substrate use efficiency by microbes would result in greater proportional retention of microbial C in SOM pools that are stabilized by organo‐mineral interactions (both of which would increase the proportion of stable SOM within total SOM).…”
Section: Introductionmentioning
confidence: 99%
“…As an extension, biochemically recalcitrant inputs would preferentially accumulate as POM (Castellano, Mueller, Olk, Sawyer, & Six, 2015). While this hypothesis has been tested and often confirmed in the laboratory (Córdova et al, 2018;Haddix et al, 2016;Lavallee et al, 2018) field experiments are still limited and largely performed in natural forest or grassland systems (Bird, Kleber, & Torn, 2008;Bird & Torn, 2006;Sokol et al, 2018;Soong et al, 2016). Understanding how differences in litter chemistry impact the decomposition and resultant SOM formation of root vs shoots is going to be critical to informing agricultural management, particularly in bioenergy production systems.…”
mentioning
confidence: 99%